Ascitic Senescent T Cells Are Linked to Chemoresistance in Patients With Advanced High-Grade Serous Ovarian Cancer - Zhang, Jie; He, Tianhui; Yin, Zhongnan; Shang, Chunliang; Xue, Lixiang; Guo, Hongyan (Frontiers in Oncology, 2022)
Senescent T cells are reported to be increased in patients with cancer and are poor prognostic indicators. However, the distribution of senescent T cells and their correlation with clinical features in high-grade serous ovarian cancer (HGSOC) is unknown. We detected the percentage of senescent T cells in the peripheral blood and ascites of patients with advanced HGSOC (n = 86) at diagnosis by flow cytometry. Compared with healthy donors, patients with HGSOC exhibited an accumulation of CD28−CD57+ (Tsen) CD8+ T cells in the peripheral blood and ascites. The frequency of Tsen CD8+ T cells in the peripheral blood was positively correlated with age and pretreatment serum CA125 and increased in patients with large volume ascites, whereas the frequency of Tsen CD8+ T cells in ascites was elevated in patients with lymph node metastasis. Patients with Tsen-high in ascites (>19.92%), but not in the peripheral blood, were more likely to be resistant to chemotherapy and had shorter progression-free survival. Tsen CD8+ T cells exhibited common senescence features including increased SA-β-gal activity, declines in proliferation, loss of CD27 and gain of KLRG-1, and the production of cytokines. In ascites, the percentage of Tsen CD8+ T cells was positively correlated with levels of interleukin-10 and granzyme B. This study suggests the potential of ascitic Tsen CD8+ T cells at diagnosis as a prognostic biomarker in HGSOC.